A study of color differences in women's ready‐to‐wear collections from world fashion cities: Intensive study of the Fall/Winter 2010 collections from New York, London, Milan, and Paris. Issue 6 (29th March 2012) - Koh, Youngrim; Lee, Joohyeon
<x xml:space="preserve">Abstract</x> The purpose of this study is to analyze the color differences in the four fashion collections from New York, London, Milan, and Paris while focusing on 2010 Fall and Winter women's ready‐to‐wear collections. The colors of the fashion collections were collected from American Vogue's website www.style.com and analyzed by using the ISCC –NBS color system which is made up of 10 basic hues of pink, red, orange, brown, yellow, olive, yellow green, green, blue, and purple, and three neutral categories of white, gray, and black. In addition to these 13 categories, yellowish pink, gold, and silver categories were classified. For analysis, one‐way ANOVA, the Scheffe test and the t‐test were adopted. The result of analysis showed that there was a statistical difference in purple compared with the other colors examined. The London collection showed the highest ratio of use in purple, whereas the Milan collection contrarily showed the lowest ratio of use in purple. © 2012 Wiley Periodicals, Inc. Col Res Appl, 38, 463–468, 2013